MEMBANGUN EKOSISTEM PENDIDIKAN HOLISTIK MELALUI KOLABORASI GURU LINTAS MATA PELAJARAN DI SD SARASWATI 6 DENPASAR - Mardika, Made; Sutriyanti, Ni Komang; Pratama, I Gede Nanda Jaya; Hermawan, I Putu Gede Wahyu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
School is a strategic place to grow the potential of the nation's generation. Every student is like a seed that has the potential to grow into a superior and character individual. In ochieving this educational goal, the role of teachers from various subjects such as Physical Education, Language, Cultural Arts, Mathematics, Science, Religion, Technology and Pancasila is crucial in creating a holistic learning ecosystem. Effective education cannot be done separately and partially, but must involve strong collaboration among teachers, with the principal as a visionary leader. With a collaborative approach based on the spirit of Ki Hajar Dewantara and the teachings of Dharma, schools can become spaces that support the growth of students' character, intelligence and spirituality. Through cross-subject synergies and integration of relevan curriculum, students not only acquire academic knowledge, but also develop skills and life values that are useful in the future. In this process, the principal plays an important role in creating a collaborative culture that optimizes students potential comprepensively. This approach results in education that not only focuses on sciencetific knowledge, but also on the formation of virtuous character, in accordance with the values of Pancasila and the noble teachings in daily life.